2012
DOI: 10.5194/acp-12-7961-2012
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cloud optical thickness and associated surface UV irradiance from SEVIRI by implementing a semi-analytical cloud retrieval algorithm

Abstract: Abstract. In this paper, we describe the implementation of the Semi-Analytical Cloud Retrieval Algorithm (SACURA), to obtain scaled cloud optical thickness (SCOT) from satellite imagery acquired with the SEVIRI instrument and surface UV irradiance levels. In estimation of SCOT particular care is given to the proper specification of the background (i.e. cloud-free) spectral albedo and the retrieval of the cloud water phase from reflectance ratios in SEVIRI's 0.6 µm and 1.6 µm spectral bands. The SACURA scheme i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…At this point the CTP and cloud pressure thickness are the only unknown variables. The cloud pressure thickness or the cloud vertical distribution has a substantial impact on the accuracy of the CTP retrievals (Carbajal Henken et al, 2015;Fischer and Grassl, 1991;Rozanov and Kokhanovsky, 2004;Preusker and Lindstrot, 2009). In this study, the cloud pressure thickness is used as an input parameter to retrieve the CTP.…”
Section: Methods 1: Lut-based Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…At this point the CTP and cloud pressure thickness are the only unknown variables. The cloud pressure thickness or the cloud vertical distribution has a substantial impact on the accuracy of the CTP retrievals (Carbajal Henken et al, 2015;Fischer and Grassl, 1991;Rozanov and Kokhanovsky, 2004;Preusker and Lindstrot, 2009). In this study, the cloud pressure thickness is used as an input parameter to retrieve the CTP.…”
Section: Methods 1: Lut-based Approachmentioning
confidence: 99%
“…For a long time, various efforts have been devoted to the study of radiative transfer in the atmosphere, including scattering, absorption, and emission (Chandrasekhar, 1960;Irvine, 1964;Ivanov and Gutshabash, 1974;van de Hulst, 1980van de Hulst, , 2012Ishimaru, 1999;Thomas and Stamnes, 2002;Davis and Marshak, 2002;Kokhanovsky et al, 2003;Marshak and Davis, 2005;Pandey et al, 2012). In this study, we develop an analytic radiative transfer equation to analyze the radiative transfer at the oxygen A and B bands.…”
Section: Methods 2: Analytic Transfer Inverse Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, it was found that for high solar zenith angles (sza) the attenuation is larger on total UV than UVer. However UVer is more attenuated in situations with small sza and cloudy or overcast conditions Pandey et al (2012). used a cloud retrieval algorithm to obtain the scaled cloud optical thickness from the SEVIRI images and than 45° (north and south) Fotiadi et al (2006).…”
mentioning
confidence: 99%